Results of the MAJORANA DEMONSTRATOR's Search for Double-Beta Decay of 76Ge to Excited States of 76Se. (February 2020) - Guinn, I.S.; Arnquist, I.J.; Avignone, F.T.; Barabash, A.S.; Barton, C. J.; Bertrand, F.E.; Bos, B.; Busch, M.; Buuck, M.; Caldwell, T.S.; Chan, Y-D.; Christofferson, C.D.; et al.
Abstract: The MAJORANA DEMONSTRATOR is searching for double-beta decay of 76 Ge to excited states (E.S.) in 76 Se using a modular array of high purity Germanium detectors. 76 Ge can decay into three E.S.s of 76 Se. The E.S. decays have a clear event signature consisting of a ββ -decay with the prompt emission of one or two γ -rays, resulting in with high probability in a multi-site event. The granularity of the DEMONSTRATOR detector array enables powerful discrimination of this event signature from backgrounds. Using 21.3 kg-y of isotopic exposure, the DEMONSTRATOR has set world leading limits for each E.S. decay, with 90% CL lower half-life limits in the range of (0.56 ‒ 2.1) ⋅ 10 24 y. In particular, for the 2 v transition to the first 0 + E.S. of 76 Se, a lower half-life limit of 0.68 ⋅ 10 24 at 90% CL was achieved.